THE EFFECT OF WORK EXPERIENCE ON REGIONAL FINANCIAL REPORTING WITH HUMAN RESOURCE (HR) COMPETENCE AS A MODERATING VARIABLE - Devi Mulia Sari; Meutia Handayani; Cut Yunina Eriva (Kajian Akuntansi, 2025)
The influence of work experience on financial reporting reflects the contribution of experience and knowledge gained by HR during work period. Meanwhile, HR competency is measured through relevant expertise and skills in managing regional finances. The combination of these factors is expected to make a positive contribution to the quality of financial reporting. The aim of the research is to provide a better understanding of how tenure and HR competency influence financial reporting in the local government environment. By understanding these factors, it is hoped that improvement and development efforts needed in HR management and Regional Financial Management Information Systems can be identified. The targeted output is the provision of policy recommendations to the local government of Banda Aceh City to improve the quality of financial reporting. The total population in this study was 44 OPDs and the number of respondents was 88 respondents. The analysis method was carried out using MRA (Moderated Regression Analysis). The results of this research show that length of service has an influence on financial reports in the Regional Financial Management information system in Banda Aceh City which is moderated by the human resource competency variable. The interaction between the use of information systems and HR competency has an effect significant to the quality of financial reports, and HR competency as a moderating variable.